Genetic variants in a lipid regulatory pathway as potential tools for improving the nutritional quality of grass‐fed beef. (13th June 2012) - Baeza, M. C.; Corva, P. M.; Soria, L. A.; Pavan, E.; Rincon, G.; Medrano, J. F.
Summary The aim of this study was to evaluate the effect of genetic variants on candidate genes corresponding to the sterol recognition element–binding protein‐1 (SREBP‐1) signaling pathway and stearoyl‐CoA desaturases (SCD1 and SCD5) on muscle fatty acid (FA) composition of Brangus steers fattened on grass. FA profiles were measured on Longissimus lumborum muscle samples using a gas chromatography–flame ionization detection technique. A total of 43 tag single‐nucleotide polymorphisms on the SCD1, SCD5, SREBP‐1, SCAP, INSIG1, INSIG2, MBTPS1, MBTPS2, and SRPR genes were genotyped on 246 steers to perform a marker–trait association study. To evaluate the influence of the Indicine breed in the composite breed, additional groups of 48 Angus, 18 Hereford, 75 Hereford x Angus, and 36 Limousin x Hereford–Angus steers were also genotyped. To perform the association analysis, FA data were grouped according to the number of carbon atoms and/or number of double bonds (i.e. SFA, MUFA, PUFA, etc.). In addition, different indexes that reflect the activity of FA desaturase and elongase enzymes were calculated. SCD1 markers significantly affected C14:1/(C14:0 + C14:1) and C18:1/(C18:0 + C18:1) indexes, whereas one SNP in SCD5 was correlated with the C16:1/(C16:0 + C16:1) index. Polymorphisms in the signal recognition particle receptor (SRPR) gene were associated with all the estimated desaturase indexes. Because the evaluated markers showed no effect on total lipid content of beef, this work supports the potential utilization of these markers for the improvement of grass‐fed beef without undesirable side effects.